THE PROFESSIONAL IN PHYSICAL EDUCATION: EXPECTATIONS AND EXPERIENCES IN THE WORK MARKET (Fiep Bulletin - online, 2011)
The paper of the permitted one in Physical Education was reorganized on the basis of the new lines of direction of the liberal activities of the profession, based on the physical evaluation, coordination, supervision, consultant, auditorship, recreate in hotel, management, management of the sport; management in leisure, bachelor in sports; physical activity and sport; science of the sport; promotion of events, sport and leisure; physical training and sports, and research applied among others. In the educational area, the study of the satisfaction in the work it assumes an uneven importance, such as, conditions of work and chances of professional growth. The data-collecting through the questionnaire was become fulfilled to verify the evaluation of the ingressions and egresses concerning the place where they would have interest to work with Physical Education. In the comparison between the distributions that register the answers of the ingressions and egresses if verify that the contact of the egresses with the professional reality made with that they became much more selective, starting to have clarity on its future intentions, mainly on the places in which they do not desire to work. This reflects, with certainty, the chances offered currently for the resume of the UnB to the students who, when participating of projects and events can investigate its vocations discovering performance fields and developing corresponding abilities that leave them prepared and premade use to act in these areas. Analyzing the other extremity it registers the preferred places in which the ingressions and egresses intend to work in Physical Education if it verifies a great inversion in the preference order, at least as for the pertaining to school Physical Education, that in the case of the ingressions appeared in 8º place, starting being the place of bigger preference of the egresses, 1º place.
Keywords: experience; expectation; market of work